Algorithmic Gharar in Islamic Banking: Reconstructing Transparency and Accountability Based on Maqasid as-Syari’ah - Muhamad Fuji Hakiki; Opik Taupik; Dodih Suhardih; Mutia Pamikatsih; Moh. Irfan Surya Solehudin (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
The rapid adoption of Artificial Intelligence (AI) in Islamic banking has transformed financing assessment, risk management, fraud detection, and customer service systems. While AI offers significant benefits in improving operational efficiency and decision-making accuracy, it also raises concerns regarding transparency, accountability, and legal responsibility in algorithm-based decisions. This study aims to analyze the concept of algorithmic gharar  in Islamic banking and reconstruct a framework for algorithmic transparency and accountability based on Maqāṣid al-Sharī‘ah. This study employs normative legal research using a library research method by examining statutory regulations, DSN-MUI fatwas, scholarly literature, and contemporary studies on AI Governance, Islamic finance, and Islamic legal theory. The legal materials were analyzed qualitatively through statute, conceptual, and maqāṣid al-Sharī‘ah approaches to construct a normative framework for algorithmic transparency and accountability in Islamic banking. The findings reveal that algorithmic opacity in AI-based decision-making may generate a new form of uncertainty referred to as algorithmic gharar , characterized by the inability of affected parties to understand, verify, or challenge algorithmic decisions. From the perspective of Maqāṣid al-Sharī‘ah, algorithmic transparency and accountability are essential to safeguard wealth (ḥifẓ al-māl), intellect (ḥifẓ al-’aql), human dignity, and social justice. This study proposes a Sharia-based AI Governance framework consisting of algorithmic transparency, human accountability, Sharia algorithm auditing, data and privacy protection, and algorithmic justice. The study contributes to the development of Islamic economic law by introducing the concept of algorithmic gharar  as a contemporary legal construct and providing a normative framework for ethical AI Governance in Islamic banking.